If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 560 + -13m = 365 Solving 560 + -13m = 365 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-560' to each side of the equation. 560 + -560 + -13m = 365 + -560 Combine like terms: 560 + -560 = 0 0 + -13m = 365 + -560 -13m = 365 + -560 Combine like terms: 365 + -560 = -195 -13m = -195 Divide each side by '-13'. m = 15 Simplifying m = 15
| 4(x+7)=-24 | | 4a-2b+5b= | | x^2+3x+5=5 | | -6+b=17 | | 7q^2-28=0 | | 2s^2+9s^2+s^2= | | x^2+28x-45173=0 | | -9(x+6)-9=-63 | | 2s^2+9s^2=s^2 | | x^2-6x+5=5 | | 4+(x+8)=2(2x+6)+20 | | 16x^2-10x-8= | | -(x+8)+9=9x+1-10x | | 37.5(x+400)=6.6666 | | 24x^2-11x-8= | | 6(3y-1)-3(2y)=26 | | 24x^2-10x-8= | | 36+x^2=100 | | -(7-m)=-(5m+7) | | 7(t-2)-t= | | 0=9a^2-4a | | 22x^2-11x-8= | | x^2+2x-4=-2x+1 | | 22x^2-10x-8= | | 22x^2-31x-8= | | -8x-11(x+5)=-2(9x+2) | | x^2+7=1 | | 40x^2+12x-28= | | 40x^2+5x-28= | | 7y+3(y-4)=3(y+1)-2 | | 4x+6=-24 | | -4(t-3)+8t=9t-2 |